Implementasi Terapi Slow Stroke Back Massage Dengan Minyak Serai Terhadap Intensitas Nyeri Kepala Penderita Hipertensi. - Damawiyah, Siti; Kamariyah, Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to analyze the effect of implementing Slow Stroke Back Massage therapy with lemongrass oil on the intensity of headaches in patients with hypertensionMethods: Â The research design used Quasy Experimental, Control Group Pre Test-Post Test Design. The population in this study were all patients with hypertension. The sample is some patients with hypertension who meet the criteria as many as 15 people in the intervention group and 15 people in the control group. The sampling technique was purposive sampling.Â Results: The results showed that from 15 respondents who were given Slow Stroke Back Massage therapy with lemongrass oil, as many as 15 respondents (100%) experienced a decrease in the intensity of headache. Decreased mean pain intensity from moderate pain level to mild pain level. Statistical test results with Mann Whitney obtained p value = 0.01, where p value <0.05, which means that there is an effect of implementing Slow Stroke Back Massage therapy with lemongrass oil on the intensity of headaches in patients with hypertension.Conclusion: Implementation of slow-stroke back massage therapy with lemongrass oil can reduce the intensity of headaches in patients with hypertension.